393 SELF-REGRESSION OF ACROMEGALY: A CASE REPORT. Issue 1 (1st January 2007) - Sahasranam, P.; Ballani, P.; Friedman, T. C.
Abstract : A 34-year-old Hispanic male with past medical history of diabetes for 2 years, on metformin, presented to his primary care physician with symptoms suggestive of carpal tunnel syndrome and fatigue. Upon workup, IGF-1 levels were found to be elevated (1290 μg/dL). A month later, he presented to the ER with complaints of an intense stabbing frontal headache, accompanied by bilateral eye pain. CT scan revealed a 1.8 cm infarcted sellar mass with acute hemorrhage. At follow-up at the endocrinology clinic, he complained of excessive sweating, a gradually progressive increase in shoe size, and symptoms suggestive of carpal tunnel syndrome. His family members had noticed some changes in physical appearance. On physical examination, he had signs of acromegaly. Three months later, he remained in remission with IGF-1 levels of 181 μg/dL. His diabetes had improved dramatically, with an HbA1c of 4.7% (HbA1C was 7.0, 6 months earlier), and a fasting plasma glucose of 68 mg/dL; metformin was thus discontinued, and he remained euglycemic. An ACTH stimulation testing ruled out adrenal insufficiency. Serum growth hormone (GH) levels after a 75 g oral glucose load were suppressed (GH levels 1.7 ng/dL, 0.3 ng/dL, 0.3 ng/dL, 0.5 ng/dL after 15 minutes, 30 minutes, 45 minutes, and 1 hour, respectively). Over the next 2 years, there was a gradual fall in IGF-1 levels into the subnormal range (80, 98 μg/dL). Biochemical testing of his gonadal axis after 13 months was consistent with hypogonadotropic hypogonadism (testosterone 291 ng/dL, LH 2.9 mIU/mL, FSH 4.7 mIU/mL). An MRI done a year after the initial study showed an empty sella with a small rim of pituitary tissue measuring 4 mm. Over the next year he had gradual regression of his acromegalic facial features and improvement in fatigue level. Conventional treatment of acromegaly includes surgical removal of the GH-producing tumor, medical therapy with octreotide or pegvisomant, and/or radiation. Here we present a case report of acromegaly that regressed following a pituitary infarction. Spontaneous resolution of GH-secreting pituitary tumors without any treatment is very rare, with only approximately 20 cases reported in the literature.